Investigation of hydrocarbon solvents for the control of paraphyn-hydrate deposits in oil wells - Liashenko, Anna (Technology audit and production reserves, 2020)
The object of research is hydrocarbon solvents for the elimination of paraffin-hydrate deposits. The chemical methods of control of paraffin-hydrate deposits, in particular, application of hydrocarbon solvents are considered in the article. Studies of the effect of various chemical reagents on the dissolution of hydrate formations using a laboratory installation at different thermo-baric regimes, closest to the real conditions of the pipe space of oil and gas wells: the temperature varied discretely from –10 to +40 °C and pressure from 0 to 10 MPa. To study the effect of hydrocarbon solvents on the process of removing hydrate formations, the most rational methods of regression analysis and mathematical planning of the experiment were used – simplex-grid planning. The G-criterion of plan optimality was used, which includes 22 experiments. The synthesis of the plan was implemented by numerical methods on a software-controlled device for information processing. The use of such methods makes it possible to reasonably organize experimental research, adjust the time, equipment, materials and perform the required number of experiments. The results of measurements are shown in the diagrams for each solvent separately. The obtained data allowed to a priori substantiate the choice of the optimal variant of application of chemical reagents for complete dissolution and removal of paraffin-hydrate formations from the surface of the internal well equipment. Analysis of the data shows that the solubility reagents butyl cellosolve and ethylacetat solvents, which can be recommended for wide application in the oil and gas industry, are characterized by the highest solubility and efficiency for removal of paraffin-hydrate deposits from the surface of well equipment. An important fact is that the consumption of the proposed solvents per оne well operation is not more than 4 m3, which is 2–3 times less than in other known analogues. The use of new solvents also allows to increase the inter-cleaning period of the well more than 2–3 times, which reduces the cost of extracted products.